2001
DOI: 10.1037/0735-7028.32.6.626
|View full text |Cite
|
Sign up to set email alerts
|

Homicide–suicide and other forms of co-occurring aggression against self and against others.

Abstract: Assessing the risk of harm to self and the risk of harm to others usually are distinct clinical processes. Yet these forms of aggression frequently coexist, occasionally with lethal outcomes. The author summarizes the literature on co-occurring aggression against self and others. Studies of homicide-suicide are reviewed first. Studies investigating the risk of co-occurring aggression against self and against others are reviewed next. The studies show a strong link between the 2 forms of aggression, etiological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
64
0
4

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(73 citation statements)
references
References 72 publications
(90 reference statements)
5
64
0
4
Order By: Relevance
“…Typically, it is used for such acts which can be assumed to be forms of aggression that are directed towards the self (Hillbrand, 2001). In the present paper, these are regarded as the behavioural manifestations of anger, which the women in this study identified as one of the emotional experiences associated with their depression (see section 4.5.1).…”
Section: Aggression Directed At Selfmentioning
confidence: 99%
See 1 more Smart Citation
“…Typically, it is used for such acts which can be assumed to be forms of aggression that are directed towards the self (Hillbrand, 2001). In the present paper, these are regarded as the behavioural manifestations of anger, which the women in this study identified as one of the emotional experiences associated with their depression (see section 4.5.1).…”
Section: Aggression Directed At Selfmentioning
confidence: 99%
“…When questioned about suicide, which can be regarded as an act of aggression that is directed towards the self (Hillbrand, 2001), most of the participants immediately denied entertaining any such thoughts or impulses, explaining that this would be wrong on two counts. Firstly, they regarded suicide as a religious sin (Evergreen: if you believe in the Lord, you're going to go to hell if you take your own life), and secondly, they believed that it would be wrong to abandon their child and family caretaking responsibilities in that way (Christine: I'm just living for my kids).…”
Section: Summary: Behavioural Manifestations Of Depressionmentioning
confidence: 99%
“…In sum, previous research supports an association of NSSI with violent behaviour toward others and suggests the presence of a subgroup of individuals who engage in NSSI that also engage in violence (Hillbrand, 2001;Maden et al, 2000;Daffern & Howells, 2009 (Chermack et al, 2000;Cunradi et al, 2002;Vanfossen et al, 2010) and academic achievement (Hoptman et al, 1999;Farrington, 1989;Swahn & Donovan, 2004), as well as relationship (Saunders, 1992;Webster et al, 1997) and employment (Gatti et al, 2007;Zagar et al, 2009;O'Leary et al, 2008) difficulties have been associated with violent behaviour. In terms of individual factors, previous work has found that ASPD features are associated with violent or aggressive behaviour toward others (Meloy, 1995), and some authors have suggested an association between antisocial personality features and NSSI behaviours (Virkkunen, 1976).…”
Section: Discussionmentioning
confidence: 91%
“…Previous research and review papers examining the association of self-injury with interpersonal violence have demonstrated associations ranging from weak to strong (Daffern & Howells, 2009;Hillbrand, 2001;Maden, Chamberlain, & Gunn, 2000). For example, approximately half of a sample of violent forensic psychiatric inpatients engaged in self-injurious behaviour (Hillbrand, 1995).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation